2020
DOI: 10.1038/s41419-020-2369-4
|View full text |Cite
|
Sign up to set email alerts
|

TNFAIP8 regulates autophagy, cell steatosis, and promotes hepatocellular carcinoma cell proliferation

Abstract: Tumor necrosis factor-α-induced protein 8 (TNFAIP8) expression has been linked to tumor progression in various cancer types, but the detailed mechanisms of TNFAIP8 are not fully elucidated. Here we define the role of TNFAIP8 in early events associated with development of hepatocellular carcinoma (HCC). Increased TNFAIP8 levels in HCC cells enhanced cell survival by blocking apoptosis, rendering HCC cells more resistant to the anticancer drugs, sorafenib and regorafenib. TNFAIP8 also induced autophagy and steat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 54 publications
(80 reference statements)
2
37
0
1
Order By: Relevance
“…TNFAIP8 is known to regulate several genes associated with cell proliferation (IL-24, FAT3, LPHN2, EPHA3), fatty-acid oxidation (ACADL), and several oncogenes, for example, NFAT5, MALAT1, MET, FOXA1, KRAS, S100P, OSTF1 35 . TNFAIP8 has been shown to inhibit cell apoptosis and increase cell proliferation in numerous cancers including lung cancer [38][39][40][41] , liver cancer 42,43 , gastric cancer 44 , esophageal cancer (ESCC) 45,46 , pancreatic cancer 47 , and prostate cancer 32,34,35 . Here we extend the analysis of the oncogenic role of TNFAIP8 and investigate the role TNFAIP8 in skin cancer cell proliferation/survival and progression.…”
mentioning
confidence: 99%
“…TNFAIP8 is known to regulate several genes associated with cell proliferation (IL-24, FAT3, LPHN2, EPHA3), fatty-acid oxidation (ACADL), and several oncogenes, for example, NFAT5, MALAT1, MET, FOXA1, KRAS, S100P, OSTF1 35 . TNFAIP8 has been shown to inhibit cell apoptosis and increase cell proliferation in numerous cancers including lung cancer [38][39][40][41] , liver cancer 42,43 , gastric cancer 44 , esophageal cancer (ESCC) 45,46 , pancreatic cancer 47 , and prostate cancer 32,34,35 . Here we extend the analysis of the oncogenic role of TNFAIP8 and investigate the role TNFAIP8 in skin cancer cell proliferation/survival and progression.…”
mentioning
confidence: 99%
“…Activated mTORC1 inhibits autophagic cascade reaction by phosphorylating ATG13 and ULK1 to block the formation of pre-initiation complex [ 13 ], and by phosphorylating ATG14 to suppress the class III PI3K activity of ATG14-containing PIK3C3 [ 14 ]. mTORC1 integrates the upstream signaling of class I PI3K/AKT [ 15 ] and adenosine monophosphate kinase (AMPK) [ 16 ] (Fig. 2 ), which can sense the nutrient status and energy levels and deliver signaling to the key downstream 4EBP1 and p70S6K, which regulate protein translation.…”
Section: Mechanisms Of Autophagymentioning
confidence: 99%
“…Abnormal expression of several genes is critical in tumorigenesis and development of HCC. Recent research has shown that tumor necrosis factor-α-induced protein 8 (TNFAIP8) increases HCC cell survival by blocking apoptosis, promoting greater resistance to the anticancer drugs sorafenib and regorafenib ( Niture et al, 2020 ). High expression of ATP/GTP binding protein like 2 (AGBL2) is associated with significantly enhanced survival and proliferation of HCC cells in vitro and tumor growth in vivo ( Wang L. L. et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%